(untitled) (Anclajes, 2023)
This article proposes a critical dialogue between New Cultural History and the Glottopolitical perspective to examine the orthographic reforms of Sebastián Díaz (1741-1813), conceiving them as normative interventions. Through a language ideologies approach to the prologue of Díaz’s encyclopedia, the analysis reveals that his orthographic reforms, which agree and conflict with the academic discourse of its time, are prescriptive practices that aimed to control the production and reception of conversation. This etiquette practice was an effect of encyclopedic instruction in early childhood, facilitated by a simplified orthography. We conclude that studying the encyclopedia was not just a means of Catholic and rational, but also linguistic disciplining.